Serum IL-18 as a predictive biomarker for acute kidney injury in sepsis patients - Pratama, Satya; Sutanto, Heri; Samsu, Nur (PT. DEKA RESEARCH INSTITUTE, 2025)
BACKGROUND: Sepsis is a syndrome that can result in multiorgan dysfunction, including acute kidney injury (AKI). AKI is a serious complication of sepsis, and its incidence ranges from 30% to 50%. Newer predictive biomarkers such as serum interleukin-18 (IL-18) are being evaluated as early diagnostic markers with potentially greater sensitivity than serum creatinine. OBJECTIVES: To evaluate the usefulness of serum IL-18 levels as a predictive biomarker for AKI in patients with sepsis. METHODS: The cross-sectional study was conducted at Dr. Saiful Anwar General Hospital and included 68 sepsis patients, 34 with AKI and 34 without AKI. The serum level of IL-18 was measured using the ELISA method. AKI diagnosis was made according to the KDIGO criteria. The Mann-Whitney test, Spearman correlation, and receiver operating characteristic (ROC) curve analysis were included in the statistical analysis. RESULTS: The results showed that serum IL-18 levels were significantly greater in the AKI group compared with the non-AKI group (49.88 ± 50.87 vs. 19.89 ± 10.40; p < 0.001). A significant positive correlation was observed between serum IL-18 levels and the risk of AKI (r = 0.505; p < 0.001). ROC analysis revealed an area under the curve (AUC) of 0.792 with 82.4% sensitivity and 64.7% specificity at a cut-off value of 23.81 pg/mL. Logistic regression revealed that with each 1-unit increase in serum IL-18, a 7.3% increase in the risk of developing AKI was observed. CONCLUSION: Serum IL-18 has good potential to serve as a predictive biomarker for AKI in sepsis patients, with reasonable diagnostic accuracy.